Diapycnal oxygen supply to the tropical North Atlantic oxygen minimum zone - Fischer, Tim; Banyte, Donata; Brandt, Peter; Dengler, Marcus; Krahmann, Gerd; Tanhua, Toste; Visbeck, Martin (Biogeosciences, 2013)
The replenishment of consumed oxygen in the open ocean oxygen minimum zone (OMZ) off northwest Africa is accomplished by oxygen transport across and along density surfaces, i.e. diapycnal and isopycnal oxygen supply. Here the diapycnal oxygen supply is investigated using a large observational set of oxygen profiles and diapycnal mixing data from years 2008 to 2010. Diapycnal mixing is inferred from different sources: (i) a large-scale tracer release experiment, (ii) microstructure profiles, and (iii) shipboard acoustic current measurements plus density profiles. From these measurements, the average diapycnal diffusivity in the studied depth interval from 150 to 500m is estimated to be 1×10−5 m2 s−1, with lower and upper 95%confidence limits of 0.8×10−5 m2 s−1 and 1.4×10−5 m2 s−1. Diapycnal diffusivity in this depth range is predominantly caused by turbulence, and shows no significant vertical gradient. Diapycnal mixing is found to contribute substantially to the oxygen supply of the OMZ. Within the OMZ core, 1.5 μmol kg−1 yr−1 of oxygen is supplied via diapycnal mixing, contributing about one-third of the total demand. This oxygen which is supplied via diapycnal mixing originates from oxygen that has been laterally supplied within the upper CentralWater layer above the OMZ, and within the Antarctic Intermediate Water layer below the OMZ. Due to the existence of a separate shallow oxygen minimum at about 100m depth throughout most of the study area, there is no net vertical oxygen flux from the surface layer into the Central Water layer. Thus all oxygen supply of the OMZ is associated with remote pathways.